أثر طريقة حل المشكلات في التحصيل لدى طالبات الصف الرابع الإعدادي في مادة التربية الاسلامية - البياتي، انتصار زين العابدين شهباز (جامعة بغداد - مركز البحوث التربوية والنفسية, 2014)
حددت الباحثة هدف البحث بتعرف أثر طريقة حل المشكلات في التحصيل لدى طالبات الصف الرابع الإعدادي في مادة التربية الإسلامية، وحددت الباحثة حدود البحث، والمصطلحات الواردة في عنوان بحثها، ومن ثم عرضت الباحثة دراسات سابقة لها صلة بموضوع دراستها فعرضت دارسات عربية وأجنبية تناولت طريقة حل المشكلات. حددت الباحثة منهجية بحثها العامة متمثلة بالمنهج التجريبي، وتكونت العينة من مجموعتين إحداهما تجريبية والأخرى ضابطة، وعملت على ضبط المتغيرات التي قد تؤثر على نتائج البحث فكافأت بين المجموعتين في مغيرات مهمة، وتوصلت إلى النتائج من خلال الوسائل الإحصائية اللازمة، وفي ضوء ما توصلت إليه الباحثة من نتائج لطريقة حل المشكلات في التحصيل نحو المادة قدمت عدداً من الاستنتاجات تركزت في فاعلية هذه الطريقة في التربية والتعليم، وقدمت عدداً من التوصيات لمن بأيديهم القرار لاستثمار هذه الطريقة الفعالة في التربية والتعليم، وقدمت عدداً من المقترحات بعدد من العنوانات استكمالاً للبحث في مجال الدراسة الحالية. The researcher identified the objective of this research Do you know the impact of the way to solve problems in the achievement of the students in the fourth grade prep Islamic Education, and the researcher has identified the limits of the search, and the terms contained in the title researched and then offered the researcher previous studies relate to the subject studied, introduced Studies in Arab and foreign countries dealt with how to solve problems, the researcher identified the methodology discussed public represented by experimental method, and the sample consisted of two groups, one experimental and the other officer, and worked on the set of variables that may affect the results between the two groups in vkavot changers task, the results reached through statistical means necessary, in the light of the findings of the researcher from the results of the way to solve problems in the article about the collection made a number of conclusions focused on the effectiveness of this method in Education, and made a number of recommendations for those with their own hands the decision to invest in this effective method of education, and made a number of proposals by a number of anwanat complement to search in the current study
Keywords: علم النفس التربوي; التحصيل الدراسي; التربية الإسلامية; القياس والتقويم التربوي